Using Coloured Cognitive Mapping (CCM) for Design Science Research - Venable, John (Springer, 2014)
Design Science Research (DSR) is a research paradigm for research that undertakes to solve general problems through the invention and evaluation of new or improved technologies. Once DSR is completed, practitioners may make use of the new technology to solve particular instances of the generalised problem (and thereby make improvements in a problematic situation). In order to effectively solve a generalised problem, it is important (among other things) for DSR researchers to (1) understand the problem, its causes, and the conditions that allow a problem to continue or hinder its solution, (2) develop a shared problem understanding among collaborating DSR researchers, (3) creatively think of alternative potential avenues and means to solve (or reduce or alleviate) the problem, and (4) develop and convey design theories about the utility of a developed design artefact to solve a problem. This paper describes how Coloured Cognitive Mapping (CCM) can be used for these purposes in the context of DSR and provides evidence of its utility for those purposes through description of an application of CCM to DSR and more formal evaluation through teaching CCM to DSR researchers and surveying them for their opinions about its utility and features.